(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2022)
The COVID-19 pandemic meant that many economies, along with their budget plans for 2020, had to be adjusted, and subsequent planned budgets for 2021 must be drafted with a dose of caution. This state of affairs applies to all countries in the world, including Saudi Arabia. Thus, the purpose of this article is to articulate the implications of the 2021 budget approved by the King of Saudi Arabia (current Salman ibn Abd al-Aziz Al Su’ud), bearing in mind the variable revenues and unpredictable expenses of the Saudi kingdom. For this purpose, a research technique was proposed, which is criticism, analysis and review of not only the literature on the subject, but mainly internet sources, which are rich in this aspect due to the current topic.